2009
DOI: 10.1038/ejcn.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

The association between maternal diet during pregnancy and bone mass of the children at age 16

Abstract: Background/Objectives: Fetal life may be a critical period for the development and/or programming of metabolic systems, including the skeleton. However, it is unclear on the association between maternal nutrition during pregnancy and bone mass in their offspring at adolescence. Subjects/Methods: This was a birth cohort study of 216 adolescents (16.2 ± 0.4 years). Dietary intake was measured by food frequency questionnaire. Bone densitometry was measured at the femoral neck, lumbar spine and total body by DXA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 28 publications
1
63
1
Order By: Relevance
“…We previously reported association between maternal diet during pregnancy, breastfeeding and bone mineral density of offspring at 8 and 16 years. [11][12][13] Therefore, the aim of this study was to use a birth cohort study to investigate the associations between maternal diet during the third trimester of pregnancy, breastfeeding and subsequent long-term body composition of offspring at 16 year.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported association between maternal diet during pregnancy, breastfeeding and bone mineral density of offspring at 8 and 16 years. [11][12][13] Therefore, the aim of this study was to use a birth cohort study to investigate the associations between maternal diet during the third trimester of pregnancy, breastfeeding and subsequent long-term body composition of offspring at 16 year.…”
Section: Introductionmentioning
confidence: 99%
“…Carmichael and co-workers showed that adequate periconception intakes of folate, vitamin B 12 , vitamin B 6 and riboflavin were associated with decreased risk of neural tube defects among Californian women (7) . Zhang's group showed that Chinese women of childbearing age with inadequate micronutrient status had a higher risk of birth defects (3) , and Yin and colleagues showed that maternal intake of Mg during the third trimester of pregnancy was predictive of bone mineral density at age 16 years (8) . Moreover, in populations where Fe deficiency is prevalent, children born to women receiving micronutrient supplementation score better in tests of intellectual function, e.g.…”
mentioning
confidence: 99%
“…LS BMD was also positively associated with maternal milk intake, calcium, and phosphorus density. With all signifi cant nutrients in the same model, fat density remained negatively associated for the FN and LS, whereas magnesium density remained positively associated for the FN [50] . In another cohort [47] , maternal magnesium intake at 32 weeks gestation was positively associated with TB BMC and BMD at age 9 years until adjusted for the child ' s height.…”
Section: Saltmentioning
confidence: 88%